Meningkatkan Berpikir Kritis dengan Model Pbl, Tai, dan Talking Stick Siswa Kelas IV SD - Helda Elisa; Tika Puspita Widya Rini (CV. ITTC INDONESIA, 2024)
The problem faced in the study is the lack of learning activity levels that affect student learning outcomes. This is due to learning that has not focused on student activity, lack of student participation in expressing opinions, and lack of understanding of the concept of the subject matter. To overcome this problem, Problem Based Learning, Team Assisted Individually, and Talking Stick models were applied. The objectives of this study were to measure teacher activity, increase student activity, develop critical thinking skills, and improve student learning outcomes. This study used a type of classroom action research with 22 students. Data analysis was done by cross tabulation method. The results of the study proved that there was an increase in each meeting from teacher activity which increased with the criteria of